Decomposition Pattern and Nutrient Dynamics in Leaf Litter of Populus deltoides Marsh. In Himachal Pradesh - Kaushal, R.; Verma, K. S.; Singh, K. N. (Indian Forester, 2006)
Decomposition rates and nutrient dynamics of Populus deltoides litter was investigated in three year old coppiced plantation situated in the mid-hills of Himachal Pradesh using the nylon net bags. Complete loss of Populus leaf litter was achieved in 20 months. The decomposition constant (k) was worked out to 1.27. Significant and a positive correlation was observed between decomposition and climatic parameters viz., rainfall and temperature (R2 = 0.61), whereas temperature did not exhibit any significant influence on the decomposition rate. Nitrogen (N), phosphorus (P), potassium (K), calcium (Ca) and magnesium (Mg) dynamics in decomposing litter revealed that concentration of nitrogen, phosphorus and calcium did not follow any specific trend during the decomposition process. Potassium and magnesium concentration, however, revealed a decreasing trend throughout the study period. Changes in absolute amount, on the other hand, followed a release pattern through the study period for N, K and Mg. P and Ca, however, depicted a three-phase pattern i.e. leaching, immobilization and release during the entire course of investigations.